Jejunal stricture in a premature infant: Is cytomegalovirus the causative pathogen or a superinfection? - Aysel ÜNLÜSOY AKSU; Sinan SARI; Ramazan KARABULUT; Özgür Ekinci; Buket DALGIÇ (Turkish Journal of Gastroenterology, 2019)
-